VD_FINDINFO HC / 2013 / 140 vom 12. Dezember 2012 - VD Tribunal cantonal (2012)
PROTECTION DE L'UNION CONJUGALE, OBLIGATION D'ENTRETIEN, SUSPENSION DE LA VIE COMMUNE | 163 CC, 176 al. 1 ch. 1 CC, 107 al. 2 LTF, 308 al. 1 let. b CPC (CH), 308 al. 2 CPC (CH)